2011
DOI: 10.1016/j.expneurol.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic dysfunction in Huntington's disease human cybrids

Abstract: In this work we studied the mitochondrial-associated metabolic pathways in Huntington's disease (HD) versus control (CTR) cybrids, a cell model in which the contribution of mitochondrial defects from patients is isolated. HD cybrids exhibited an interesting increase in ATP levels, when compared to CTR cybrids. Concomitantly, we observed increased glycolytic rate in HD cybrids, as revealed by increased lactate/pyruvate ratio, which was reverted after inhibition of glycolysis. A decrease in glucose-6-phosphate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…We demonstrated a reduced NADH level and NADH/NAD+ ratio in the mouse models. This may be an indication of redox imbalance, and could suggest an inherent dysfunction of mitochondria, or be indicative of alterations in a mitochondrial function upstream of oxidative phosphorylation [50]. In particular, this could indicate a disrupted efficiency of the Krebs cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated a reduced NADH level and NADH/NAD+ ratio in the mouse models. This may be an indication of redox imbalance, and could suggest an inherent dysfunction of mitochondria, or be indicative of alterations in a mitochondrial function upstream of oxidative phosphorylation [50]. In particular, this could indicate a disrupted efficiency of the Krebs cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It is also accepted that mutant Htt not only impairs mitochondrial function, but also compromises cytosolic and mitochondrial calcium homeostasis. This ultimately contributes to neuronal dysfunction and death in HD (Ferreira et al, 2011). Mitochondria are the main cellular source of ROS and key regulators of cell death.…”
Section: Groups Remarksmentioning
confidence: 99%
“…The mutant Htt causes cell death by a variety of mechanisms. It causes mitochondrial dysfunction by interacting with the organelle and producing defects in the dynamics of the mitochondria which, in turn, may result in bio-energetic failure (Ferreira et al, 2011). Studies have demonstrated reduced activity of the complex II enzyme succinate dehydrogenase (SDH), a 55-60% decrease in complex II-III activity in the basal ganglia of patients with Huntington's disease decrease along with a decrease in complex IV activity in HD striatum (Leegwater-Kim and Cha, 2004).…”
mentioning
confidence: 99%
“…Recapitulation of mitochondrial disorders in cell culture has largely relied on cytoplasmic hybrid cells or cybrids, in which the mitochondrial content of a host cell has been manipulated such that endogenous mtDNA has been depleted and repopulated with donor mtDNA from platelets or enucleated cells [37,38]. Cybrids have been used to characterise the disturbances in cellular bioenergetics LHON is caused by mutations in genes encoding components of the mitochondrial respiratory NADH-ubiquinone oxidoreductase complex (complex I).…”
Section: Cellular Models Of Mitochondrial Diseasementioning
confidence: 99%